Antidotarium Nicolai: sua posição no movimento literário médico nos séculos XII e XIII - Stacheski, Mônica Soares (2017)
Antidotarium Nicolai is a collection of recipes of composite medicines probably written about 1180 in Salerno, southern Italy, was related to the medical literary movement originated in the School of Salerno. Its author remains unknown, although the manuscript begins stating “Ego, Nicolaus” (I, Nicholas). It was written for the author’s colleagues, i.e., practicing doctors, or students as a practical book on the preparation of medicines. Copied in hundreds of manuscripts and printed as incunabula and books, Antidotarium Nicolai circulated across medical schools outside Italy starting at the end of the 13th century. It was included both officially and unofficially in the syllabus of European university courses along the Middle Ages and modern times. The present study discusses the historical-social context, secondary literature and primary sources closest to Antidotarium Nicolai and analyzes its content from the perspective of history of science